Empowerment Program for a Poor Elderly Group in Boyolali, Indonesia - Hidayati, Nurul; Sudarmo, Sudarmo; Wahyunengseh, Rutiana Dwi (KnE Social Sciences, 2022)
This study aimed to strengthen the participation of a poor elderly group in a community-based empowerment program at the PKH Elderly Garden located in Andong District, Boyolali Regency, Indonesia. Old age is the final stage of the human development cycle and is a natural and unavoidable process. Psychological, physical, social, and economic changes are experienced by the elderly. So far, there have not been many similar studies focusing on strengthening the participation of the elderly in the context of social change in development. Qualitative methods were used with a case study approach. The results demonstrated that social engagement was the most important social capital for optimizing roles, building trust, respecting differences, providing tolerance, and increasing self-confidence in empowering the elderly group. Participation of the elderly in the program could have a positive impact on their psychological, physical and socio-economic characteristics, through good communication, socialization, mobilization, and personal contribution. In addition, social assistants had an important role as enablers, facilitators, dynamists, mediators, and motivators. Keywords: elderly group, social engagement, community empowerment